Optimization of Formula Film based on Amylopectin Cassava Starch and Carrageenan as a Raw Materials of Capsule Shell - G Jeni christi A; Laksmi Ambarsari; Heri Purwoto (Current Biochemistry, 2016)
Capsules are very important in the packaging of pharmaceutical preparations. Commercial capsule shell is generally made of gelatin from cows and pigs. Alternatives to gelatin from non-animal raw materials can be obtained from polysaccharides like starch and carrageenan. The purpose of this study was to obtain the optimum formula between amylopectin and carrageenan as a raw material subtitute for gelatin capsule shell. Program Design Expert 7.0.0 (trial version) with Response Surface Methodology (RSM) Central Composite Design was used to optimize formula with three variable factors and three response variables. Based on the analysis by determining the adjusted range, program recommends 29 optimization solution with desirability value 1. Formula 6 and 28 was selected for validation with factors 1,01% of amylopectin, 1.01% of carrageenan, 2.17% of glycerin (formula 6) and 3.00% of amylopectin, 2.00% of carrageenan, 2.90% of glycerin (formula 28). Prediction response value was 12.94% of moisture content, 6.35% of ash content (formula 6) and 12.99% of moisture content, 8.67% of ash content (formula 28). Validation result value was 21.45% of moisture content, 7.58% of ash content, 6.12 minutes of solubility in water (formula 6) and 17.67% of moisture content, 7.78% of ash content, 9.30 minutes of solubility in water.